2014
DOI: 10.1179/1743284713y.0000000399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B on hot ductility of high Al, TWIP steels

Abstract: The influence of B on the hot ductility of high Al, Ti containing twinning induced plasticity (TWIP) steels has been examined. It was established that provided the B was fully protected by adding sufficient Ti to combine with all the N, then B could segregate to the austenite grain boundaries and improve ductility. This improvement was particularly marked for the temperature range of 700–900°C, the range in which the straightening operation often takes place in continuous casting. Of most importance in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Thereby, because of the non-equilibrium segregation of boron at grain boundaries during the steel solidification, formation of the second-phase precipitates is promoted, whose nature may be as compounds of the type M 23 (B,C) 6 , Fe 2 B, M 3 (B,C) [32,57] and even C x B y , localized both inside and at grain boundaries of the austenite. Similar results were obtained in the research work of Kang et al [28] in TWIP steels containing different boron concentrations. They argued the improvement in the hot ductility at the temperature range of 700-800°C is associated with the presence of BN and Fe 23 (B,C) 6 at grain boundaries.…”
Section: Evaluation Of Ti and B Additions On Hot Ductilitysupporting
confidence: 91%
See 3 more Smart Citations
“…Thereby, because of the non-equilibrium segregation of boron at grain boundaries during the steel solidification, formation of the second-phase precipitates is promoted, whose nature may be as compounds of the type M 23 (B,C) 6 , Fe 2 B, M 3 (B,C) [32,57] and even C x B y , localized both inside and at grain boundaries of the austenite. Similar results were obtained in the research work of Kang et al [28] in TWIP steels containing different boron concentrations. They argued the improvement in the hot ductility at the temperature range of 700-800°C is associated with the presence of BN and Fe 23 (B,C) 6 at grain boundaries.…”
Section: Evaluation Of Ti and B Additions On Hot Ductilitysupporting
confidence: 91%
“…Actually, few work has been done about the study of the hot ductility behavior of TWIP steels [21][22][23][24][25][26][27][28], taking into account various experimental parameters, where the most significant is the microstructural conditioning before tensile testing. Generally, the results of these research works have shown a decrease of the hot ductility in the temperature range of 700-1000°C due to the AlN precipitation and the high Mn content (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7) P. Lan et al have analyzed the solidification microstructure, solidification defects, thermophysical properties and hot ductility of Fe-22Mn-0.7C TWIP steel ingot. [8][9][10][11][12] S. E. Kang et al [13][14][15][16][17][18] have investigated the influences of composition and AlN on the hot ductility of high aluminum TWIP steels, which were produced by 50 kg vacuum induction furnace. I. Mejía, 19) A. E. Salas-Reyes 20) and A. S. Hamada 21) have studied the hot ductility behavior of high-manganese aus-tenitic TWIP steels.…”
Section: Introductionmentioning
confidence: 99%